Redefining postmastectomy radiation contouring in the era of immediate breast reconstruction: An accurate assessment of local recurrence risk. (July 2021) - Lao, Nicholas; Brackstone, Muriel; Formenti, Silvia C.; Doherty, Christopher; Perera, Francisco; Chow, Ronald; DeLyzer, Tanya; Grant, Aaron; Boldt, Gabriel; Lock, Michael
Highlights: Breast cancer recurrences deep to pectoralis are very rare after mastectomy. Post-mastectomy chest wall radiation should exclude deep chest wall structures. Radiation after immediate implant reconstruction increases complications. Post-mastectomy radiation should target subcutaneous tissues and pectoralis major. Abstract: Introduction: Most studies report post-mastectomy local recurrences as chest wall recurrences without clarifying whether the recurrence is in the subcutaneous tissue, muscle or underlying rib. Post-mastectomy chest wall radiation is recommended in patients at increased risk of locoregional recurrence. Chest wall radiation-related fibrosis has become an important clinical consideration in the era of immediate implant-based breast reconstruction. In patients with commonly performed subpectoral implant-based reconstruction, the pectoralis major becomes relocated anterior to the implant and just deep to skin, therefore raising the question of value in radiating deep chest wall structures. This study assessed the rate of recurrence in each anatomical region of chest wall in post-mastectomy patients. Methods: A comprehensive breast cancer database of 4287 patients at a single regional cancer center from 2006 to 2018 was retrospectively analyzed to identify 1571 mastectomy patients. Recurrences were classified as local skin/subcutaneous, pectoralis muscle (pectoralis major), deep chest wall (pectoralis minor, intercostal muscle or rib) or regional axillary recurrence. Results: A total of 26 patients with locoregional recurrence were identified. Most recurrences were in the skin/subcutaneous level. Of 1571 mastectomy patients, only one patient developed a local recurrence posterior to pectoralis major. Our literature search and meta-analysis revealed that local recurrences post-mastectomy are much more likely to be in subcutaneous tissues/pectoralis major versus deeper chest wall. Conclusion: A reduced clinical target volume which encompasses skin/subcutaneous and pectoralis muscle layers without treating deep chest wall may be more appropriate to reduce radiation-associated toxicity since avoiding circumferential radiation of an implant may prevent capsular contracture without compromising treatment benefit.